The role of macro- and microtoponyms in problems solving of the ancestral homeland of the Slavs - Лучик, Василь (Geographical names in physical space, 2016)
Ancient macro- and microtoponyms play an important role in the establishment of the fatherland of the Slavs. Thus the entire complex of extra-linguistic and endo-linguistic factors must be taken into consideration in the process of searching the antique cradle of the Great Slavs as an ethnos.